Are the decisions of the american judges in "hard cases" efficient? : The empty answers provided by the economic analysis of law - Martínez Cinca, Carlos Diego (Derecho Público Iberoamericano, 2013)
The arguments advanced by Richard Posner and the Law & Economics movement in the last forty years for an alleged rational behavior of the Common Law Judges and its evolution towards efficiency are analysed and discussed in this paper. It focuses on both “normative” and “positive” approach of the economic analysis of judicial behaviour. The analysis shows some inconsistencies in Posner’s own theory.